2012
DOI: 10.1111/j.1365-2702.2012.04276.x
|View full text |Cite
|
Sign up to set email alerts
|

Frontline healthcare providers’ views of depression and its prevention in older adults

Abstract: Study findings show how family, Chinese culture and socio-economic circumstances influence accounts of depression and its prevention in older adults. Attention to the cultural construction of meanings may help extend our vision beyond a focus on the biomedical discourse and promote innovative ways of tackling depression that match the policy goals with the needs of older adults and community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 25 publications
(40 reference statements)
0
20
0
Order By: Relevance
“…Our findings lend further support to the critical roles of both intergenerational solidarity and conflicts in older adults’ mental health. Previous observations indicated that the main contributor to depression in older adults was the lack of their children's support, and that lack of support was related to reduced solidarity and increased discordance in the intergenerational relationships, including children not taking care of aged parents, the prevalence of intergenerational conflicts and reduced intergenerational interactions (Lu & Hsieh, ). Consistently with previous studies (Katz, ; Lang & Schütze, ), our study also highlights the importance that consensual‐normative solidarity and affectual closeness have in intergenerational relationships, which have been associated with depression either partially or fully through the older parents’ feelings of loneliness and loneliness‐related insomnia symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings lend further support to the critical roles of both intergenerational solidarity and conflicts in older adults’ mental health. Previous observations indicated that the main contributor to depression in older adults was the lack of their children's support, and that lack of support was related to reduced solidarity and increased discordance in the intergenerational relationships, including children not taking care of aged parents, the prevalence of intergenerational conflicts and reduced intergenerational interactions (Lu & Hsieh, ). Consistently with previous studies (Katz, ; Lang & Schütze, ), our study also highlights the importance that consensual‐normative solidarity and affectual closeness have in intergenerational relationships, which have been associated with depression either partially or fully through the older parents’ feelings of loneliness and loneliness‐related insomnia symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Depression among older adults is underlain by various experiences of loss and maladaptation to distressing life circumstances in late life, including health problems, issues with cognitive functioning and psychosocial isolation (Almeida, ; Hall & Reynolds, ; Lu & Hsieh, ). In this way, depression among older adults, unlike young people, is strongly influenced by the developmental stage of old age and, accordingly, can be considered as a typical reaction due to ageing, or else as the effect of other healthcare problems or medical illnesses, and frequently presents with atypical symptoms (Fiske, Wetherell, & Gatz, ; Vieira, Brown, & Raue, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies reflected both publicly funded and insurance-based systems. Qualitative data were mostly collected via interviews 18,19,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] and/or focus groups 34,39,[43][44][45][46] with two ethnographic studies, 47,48 one conference and nominal group technique, 49 one mixedmethods survey, 50 and one multiple case study. 51 Two-thirds of studies were of good/ very good overall quality (Table 1); most met the checklist criteria and the vast majority were well reported ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Late-life depression was felt to lack suitable therapeutic solutions as it was considered to mainly arise from 'justifiable' causes, many of which related to ageing. The majority of HCPs across all countries primarily attributed late-life depression to difficult social circumstances and, in particular, age-related social issues (for example, loneliness or bereavements) and/or physical health issues, frailty, and functional decline: 18,19,[32][33][34]37,[39][40][41][42][43][44]51 'GPs described depression as part of a spectrum including loneliness, lack of social network, reduction in function, and very much saw depression as "understandable" and "justifiable".' 19 Many GPs and nurses, therefore, felt there was a definite difference between sadness or distress that 'understandably' related to these issues, and clinical depression, but rarely defined where this border lay.…”
Section: Avoidance Of Medicalisation Of Social Circumstancesmentioning
confidence: 99%